Fumaria parviflora regulates oxidative stress and apoptosis gene expression in the rat model of varicocele induction. (29th September 2020) - Dolatkhah, Mohammad Amin; Shokoohi, Majid; Charvandeh, Sheida; Tvrda, Eva; Shoorei, Hamed; Moghimian, Maryam; Alihemmati, Alireza
Abstract: Varicocele is one of the leading causes of male infertility in which oxidative stress induces DNA damages in spermatozoa of patients with varicocele. Recent studies indicated that the treatment with antioxidant agents has protective effects against the formation of reactive oxygen species (ROS). Our research aimed to evaluate the impact of Fumaria Parviflora (FP) on the varicocele‐induced testicular injury. For this purpose, 32 adult male Wistar rats ( n  = 8 per group) were randomly assigned to four groups as follows: sham group, varicocele group, varicocele treatment group and the control treatment group. The experimental groups daily received FP (250 mg/kg) for 8 weeks. The induction of varicocele was conducted by partial occlusion on the left renal vein. The diameter of seminiferous tubules, Johnsen's score and the epithelium thickness improved in the treated‐varicocele group as compared to the varicocele group. FP extract could increase the biochemical parameters including superoxide dismutase and glutathione peroxidase, and also decrease malondialdehyde level in the varicocele group. Furthermore, varicocele markedly increased both mRNA and intensity of Bax, while treatment with FP could alleviate them. We concluded that FP could alleviate varicocele, possibly by lowering oxidative stress and testicular damage.